The prevalence of headache in German pupils of different ages and school types - Nieswandt, Vera; Richter, Matthias; Berner, Reinhard; Hagen, Maja von der; Klimova, Anna; Roeder, Ingo; Koch, Thea; Sabatowski, Rainer; Goßrau, Gudrun (Cephalalgia, 2019)
Background/objective: Headache in pupils is underestimated and has a negative impact on learning and life. The aim of this study was to investigate headache prevalence and its collateral effects, in pupils of different ages and school types in a German city.MethodsAnonymized questionnaires were distributed to 5419 pupils attending primary and secondary schools. Demographics, headache frequency, analgesic use, school absence and, for secondary school children, data on lifestyle were collected. Results: The questionnaire was returned by 2706 children (49%), 1362 (50.3%) girls, 1344 (49.7%) boys. Of these, 36.6% indicated a frequency of 1, and 31.5% a frequency of?≥?2 headache days per month within the last 3 months. Headache prevalence increased with school grade, age and secondary school type: 63.6%, 67.2% and 79.5% for primary school children, pupils attending 8-year and pupils attending 6-year secondary schools, respectively. With secondary school level I certificates, pupils are prepared for general professional training in 6 years. Secondary school level II results, after 8 years of training, in university entrance level II certificates, which are the precondition for university studies. Girls reported significantly more headache than boys (73% vs. 63.1%). A significant relationship has been observed between headache frequency and school absence and between headache intensity and headache frequency. Of pupils with headache at least twice a month, 48.1% reported analgesic intake. Ibuprofen (49.1%) and paracetamol (32.8%) were the most frequently used analgesics. Of those pupils with headache?≥?2 days/month, 68.3% did not have a specific headache diagnosis. Concomitant diseases and regular drug intake, analgesic intake for another reason than headache, caffeine consumption and lack of participation in sports were positively correlated with headache. Conclusions: The majority of pupils suffer from headache at least once a month. Since frequent headache results in educational and social limitations, pupils at risk should be identified and referred to headache education programs. Efforts are needed to improve the management of juvenile headache patients.